Electrohydraulic lithotripsy through endoscopic retrograde cholangiopancreatography combined with SpyGlass in the treatment of complex pancreatic duct stones: A case report and literature review - Pu, Weigao; Ma, Chenhui; Wang, Bofang; Wang, Yunpeng; Wang, Haiyun; Xu, Bo; He, Puyi; Cui, Hongbin; Chen, Hao (Frontiers in Surgery, 2023)
The incidence of pancreatic duct stones (PDS) is less than 1%. After the formation of stones, the lumen of the pancreatic duct is blocked, and the pancreatic juice cannot be discharged smoothly, resulting in the impairment of the internal and external secretion of the pancreas, aggravation of chronic pancreatitis, and even the occurrence of pancreatic cancer. Surgery usually involves incision of the pancreatic parenchyma, incision of the pancreatic duct to find the pancreatic duct, and removal of the stone for pancreaticojejunostomy. Although surgical treatment is similar to endoscopic treatment in terms of clinical relief, surgical treatment is invasive and is associated with many complications. Several national guidelines now recommend endoscopic retrograde cholangiopancreatography (ERCP) as the treatment of choice for PDS. The emergence of SpyGlass makes it possible to directly visualize the ERCP blind area of the pancreatic system. Electrohydraulic lithotripsy (EHL) under SpyGlass can crush large and pressure-resistant stones into smaller fragments, significantly improving the success of endoscopic treatment of large stones rate. Here, we report a patient with PDS who underwent ERCP combined with Spyglass electrolithotripsy, avoiding surgery, reducing trauma, and being discharged from the hospital with a rapid recovery. Therefore, endoscopic therapy is effective and safe for PDS patients. The combination therapy of this patient is the first use of SpyGlass for PDS in our center, which marks a new stage in the application of endoscopic therapy for pancreatic diseases.